2018
DOI: 10.2118/182609-pa
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Expected Uncertainty Reduction and Value of Information Using Ensemble-Variance Analysis

Abstract: Summary Data-acquisition programs, such as surveillance and pilots, play an important role in minimizing subsurface risks and improving decision quality for reservoir management. For design optimization and investment justification of these programs, it is crucial to be able to quantify the expected uncertainty reduction and the value of information (VOI) attainable from a given design. This problem is challenging because the data from the acquisition program are uncertain at the time of the ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Satija and Caers [42] used the same approach in a reservoir problem and concluded that the method provided uncertainty estimates of production forecast in reasonable agreement with rejection sampling. More recently, He et al [22] used similar ideas from DSI to estimate the uncertainty reduction in a study to compute the value of information of data-acquisition plans. Jeong et al [24] applied machine learning techniques (neural networks and support vector regression) to DSI.…”
Section: Introductionmentioning
confidence: 99%
“…Satija and Caers [42] used the same approach in a reservoir problem and concluded that the method provided uncertainty estimates of production forecast in reasonable agreement with rejection sampling. More recently, He et al [22] used similar ideas from DSI to estimate the uncertainty reduction in a study to compute the value of information of data-acquisition plans. Jeong et al [24] applied machine learning techniques (neural networks and support vector regression) to DSI.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach builds on work in other disciplines in which uncertainty quantification and reduction are applied to understand or improve the behavior of domain-specific models. For example, in petroleum engineering, an ensemble-based approach is used to derive value of information (VOI) estimates for resolving parameter values in models of oil reservoir management (He et al, 2018). In this setting, a company may be interested in performing the experiment or analysis needed to improve their certainty in a model of profit gain or risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach builds on work in other disciplines in which uncertainty quantification and reduction are applied to understand or improve the behavior of domainspecific models. For example, in petroleum engineering, an ensemblebased approach is used to derive value of information (VOI) estimates for resolving parameter values in models of oil reservoir management (He et al, 2018) . In this setting, a company may be interested in performing the experiment or analysis needed to improve their certainty in a model of profit gain or risk.…”
Section: Discussionmentioning
confidence: 99%